Well-known but unsung - Tan, Samuel K. (1999)
In the Philippines, as elsewhere, armed struggles involved all classes in society directly or indirectly limited or wholly. Only its leadership has been identified with the elite or ilustrado initially or otherwise. Its success or failure has, therefore, been attributable to the class character of the elite. In the Sulu part of the Muslim (Bangsamoro) struggle, which is the context of this paper, all the revolts against colonialism or neo-colonialism in Sulu history were led by the local elite called datu, panglima, maharajah, nakib, rajah, imam, ulangkaya, and, to a certain extent, the Sultan or Rajah Muda. Exceptions have been limited to small messianic bands usually influenced by some unexplainable cultic influences. One of the most bloody and localized internal wars against colonialism and its local allies took place during the last decade of Spanish rule in Sulu when Spanish presence became quite obvious after the establishment of Spanish military forts following Malcampo's expedition in 1876. The death of Badaruddin II in 1884 brought about a politically bloody civil war between the Patikul datus led by Datu Aliyuddin and the Maimbung-based datus led by Amirul Kiram, with the assistance of his astute mother, Inchi lamila, wife ofSultan lamalul Alam. Eventually, Datu Harun Narrassid entered the political contest in 1886 with encouragement from the Spanish government. He became the Sultan recognized by Spain and immediately started the violent opposition from both the Aliyuddin and Kiram factions. By 1890,Island. Ultimately, Sultan Harun was compelled to resign and accept the ascension of Amirul Kiram as Sultan lamalul Kiram II in 1893. If bloody and sustained resistance is to be used as an index of heroism, Amirul Kiram deserves to be a hero. If contribution thru non-violent but equally important means of resistance is to be included in the criteria of heroism, then about 150 Jawi letters of Kiram deserve to be mentioned as worthy of praise, being materials full of strong and, sometimes, angry indictment of American rule in Sulu. Unfortunately, Amirul Kiram has not been given the honor he deserves as one of Sulu's heroes because of his high position. But laying aside class criteria, this unsung hero deserves a place in revolutionary history. One has only to read his numerous correspondences to feel his intense love for liberty.